Thymus vulgaris L. and thymol assist murine macrophages (RAW 264.7) in the control of in vitro infections by Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans - de Oliveira, Jonatas Rafael [UNESP]; Figueira, Leandro Wagner [UNESP]; Sper, Fábia Lugli [UNESP]; Meccatti, Vanessa Marques [UNESP]; Camargo, Samira Esteves Afonso [UNESP]; de Oliveira, Luciane Dias [UNESP] (Springer Nature, 2017)
Abstract: Microorganisms are capable to combat defense cells by means of strategies that contribute to their stabilization and proliferation in invaded tissues. Frequently antimicrobial-resistant strains appear; therefore, alternative methods to control them must be investigated, for example, the use of plant products. The capacity of the thyme extract (Thymus vulgaris L.) and phytocompound thymol in the control of in vitro infections by Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans in murine macrophages (RAW 264.7) was evaluated. Minimal inhibitory concentrations (MIC) of the plant products were used. The effect of these MIC were analyzed in the assays of phagocytosis and immunoregulation by analysis of the production of cytokines (IL-1β, TNF-α, and IL-10) and nitric oxide (NO). The plant products effectively assisted the macrophages in the phagocytosis of microorganisms, presenting significant reductions of S. aureus and P. aeruginosa. The macrophages also regulated the production of inflammatory mediators in the infections by S. aureus, P. aeruginosa, and C. albicans. In addition, thyme provided a satisfactory effect in response to the bacterial infections, regarding generation of NO. Thus, the effectiveness of the thyme and thymol to control in vitro infections by S. aureus, P. aeruginosa, and C. albicans was observed. Highlights: Phagocytosis of S. aureus by RAW 264.7 was enhanced with thymolThyme enhanced the phagocytosis of P. aeruginosa by RAW 264.7Plant products provided immunoregulation of inflammatory cytokinesProduction of nitric oxide was improved with the treatments in bacterial infections.
Keywords: Candida albicans; In vitro infection; Pseudomonas aeruginosa; Staphylococcus aureus; Thymol; Thymus vulgaris